Digital Detox Strategy for Schools and Families to Strengthen Students' Religious Character - Faizatul Widat; Rizki Naimah (Al-Qalam Institue, 2026)
The rapid development of digital technology has affected the social life and character formation of the younger generation, especially in students’ religiosity. Excessive use of digital devices risks shifting spiritual values, lowering the quality of self-reflection, and reducing direct interaction. This research aims to develop and evaluate digital detox strategies that involve schools and families in strengthening students’ religious character. The method used is qualitative research with a case study design at school. Data was collected through interviews, observations, and documentation. The results of the study show that collaboration between schools and families in limiting technology use and strengthening religious values has been effective in strengthening students’ religious character, increasing focus on learning, and reducing dependence on digital technology. This research contributes to the development of a digital detox model that is not only restrictive but also educational and transformative. In practice, this study guides schools and families in designing technology management programs oriented towards strengthening religious character.